SURGICAL TREATMENT OF RECURRENT MULTI-NODULAR CERVICOTHORACIC GOITER - Elena A. Ilicheva; Daria V. Lebedeva; Eugene G. Grigoryev (Байкальский медицинский журнал, 2024)
Relevance. Misdiagnosis of retrosternal goiter occurs in 0,2 to 45 % of patients.Case descriptions.  The authors present a case of recurrent cervical goiter from cervical exposure 34 years after the first surgical intervention. The reason for the goiter recurrence was considered as an inadequate previous surgery. In the presented case report, the node extended retrosternally to a depth of 8 cm, was fused to the paratracheal tissue, was supplied with blood from the right internal thoracic artery and was intimately adjacent to the aortic arch, which complicated surgical intervention from the classical approach. An atypical course of coronary heart disease was described as a manifestation of recurrent thyrotoxicosis. The lack of effect from conservative therapy for “cardiogenic” pathology could be due to the intrathoracic location of the goiter and the occurrence of subclinical thyrotoxicosis.Surgical intervention is reasonable to perform in the extent of thyroidectomy with mandatory removal of intra-thoracic nodes with the elimination of all symptoms of thyrotoxicosis. A retrosternal goiter with a spread below the aortic arch can be removed from the cervical exposure.